Melatonin and Human Cardiovascular Disease - Pandi Perumal, Seithikurippu R. (2016)
The possible therapeutic role of melatonin in the pathophysiology of coronary artery disorder (CAD) is increasingly being recognized. In humans, exogenous melatonin has been shown to decrease nocturnal hypertension, improve systolic and diastolic blood pressure, reduce the pulsatility index in the internal carotid artery, decrease platelet aggregation, and reduce serum catecholamine levels. Low circulating levels of melatonin are reported in individuals with CAD, arterial hypertension, and congestive heart failure. This review assesses current literature on the cardiovascular effects of melatonin in humans. It can be concluded that melatonin deserves to be considered in clinical trials evaluating novel therapeutic interventions for cardiovascular disorders.